The Impact of Probiotic Supplementation on Sports Achievement - Literature Review - Basiak, Aneta; Suława, Adrian; Fedorowicz, Sebastian; Targoński, Oskar; Targońska, Marta; Furgalska, Julia; Ptasiński, Aleksander; Niekurzak, Rafał; Buczek, Agnieszka (Quality in Sport, 2024)
INTRODUCTION: According to the official definition provided by the Expert Consultation of the Food and Agricultural Organization of the United Nations and the World Health Organization (FAO/WHO), probiotics are "Live microorganisms that, when administered in adequate amounts, confer a health benefit on the host”. Currently, science focuses on understanding the physiological and metabolic mechanisms occurring during intense physical activity. Research has begun on supporting the intestinal microbiome to achieve better results in sports. PURPOSE OF THE WORK: This work aims to present interesting research on the potential role of probiotics in athletes. It illustrates how probiotics act on the body through many different mechanisms, which result in what is most important: homeostasis. The main intention is to demonstrate the potential power of probiotics, which will allow us to compose personal probiotics to achieve better results in sports in the future thanks to the design of personalized probiotics. DESCRIPTION OF THE STATE OF KNOWLEDGE: Recent research has shown the positive effect of probiotics on the processes occurring in the body. They reduce inflammatory parameters and oxidative stress, improve the tightness of the intestinal barrier, have immunomodulatory properties, and regulate the functioning of skeletal muscles, bones and other groups of organs. Thanks to the use of appropriately composed probiotics containing specific bacterial strains, the body’s regeneration is shorter and the effectiveness of exercises is greater. CONCLUSIONS: The presenting research results may be a turning point in researching probiotics’ mechanism of action. Further probiotic research should optimize supplementation composition, dose, and duration to obtain maximum safety and health benefits.